(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the modern world, artificial intelligence technologies have brought significant development to numerous industries, but they also create challenges to fundamental human rights, especially privacy and freedom. In this article, the complex relationship between AI and human rights is investigated while examining global agreements, declarations, empirical studies, and factual evidence to elucidate the impact of AI on privacy rights. Also, it emphasized the necessity for robust regulatory frameworks and ethical standards to mitigate risk and safeguard rights.